Nano-cellulose based nano-coating biomaterial dataset using corn leaf biomass: An innovative biodegradable plant biomaterial - Sharif Hossain, A.B.M.; Uddin, Musamma M.; Veettil, Vajid N.; Fawzi, Mohammad (Elsevier, 2018)
The nanocellulose derived biodegradable plant biomaterial as nano-coating can be used in the medical, biomedical cosmetics, and bioengineering products. Bio-plastic and some synthetic derived materials are edible and naturally biodegradable. The study was conducted to investigate edible nano-biopolymer based nano-coating of capsules and drugs or other definite biomedical materials from corn leaf biomass. Corn leaf biomass was used as an innovative sample to produce edible nano-coating bioplastic for drug and capsule coating and other industrial uses. The data show the negligible water 0.01% absorbed by bio-plastic nanocoating. Odor represented by burning test was under the completely standard based on ASTM. Moreover, data on color coating, tensile strength, pH, cellulose content have been shown under standard value of ASTM (American standard for testing and materials) standard. In addition to that data on the chemical element test like K+, CO3 −−, Cl- Na+ exhibited positive data compared to the synthetic plastic in the laboratory using the EN (166)) standardization. Therefore, it can be concluded that both organic (cellulose and starch) based edible nano-coating bioplastic may be used for drug and capsule coating as biomedical and medical components in the pharmaceutical industries.